Analisis Penerapan Nilai Pendidikan Karakter Pada Pembelajaran Biologi Era Society 5.0 Pada Siswa Kelas X MAN Binjai - Nadia, Rizka Lucy; Ulfa, Syarifah Widya; Suryani, Ira (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the application of character education values in biology learning in the era of society 5.0 for class X students of MAN Binjai. This study uses a mixed methods approach with a sequential exploratory design, namely a combination research method that combines qualitative and quantitative research methods sequentially. Data collection techniques are carried out using case studies and experiments. Case studies use instruments, namely documentation, interviews and observations of biology teachers. While the experiment uses a student needs questionnaire instrument. The results of the study indicate that the application of character education values in biology learning in the era of society 5.0 for class X students of MAN Binjai that have been developed, in character education the highest score with a value of 89% in the aspect of tolerance character values, a medium score with a value of 60% in the aspect of health care character values and the lowest score with a value of 42% in the aspect of environmental care. The obstacles faced by biology teachers are that students still do not carry out the tasks and obligations given by the teacher with full responsibility, students do not submit assignments on time.